PEMBERHENTIAN WALIKOTA YANG MELAKUKAN KASUS KORUPSI DAN WEWENANG PELAKSANA TUGAS WALIKOTA (STUDI DI KOTA BEKASI, JAWA BARAT): Dismissal of Mayors who Commit Corruption Cases and the Authority of the Acting Mayor (Study in Bekasi City, West Java) - Fahtimah, Trisinta Nurul; Purnomowati, Reni Dwi (AMICUS CURIAE, 2024)
The position of Mayor is a very risky position if there is a vacancy, so if there is an issue of offence thatcauses a vacancy, a temporary replacement must be made first. Similar to what happened in Bekasi City,when the mayor was fired for corruption. The subject matter is how the mechanism for dismissing themayor of Bekasi who committed a criminal offence according to Law No. 23 of 2014 concerningRegional Government and whether the Acting Mayor of Bekasi is in accordance with Law No.23 of 2014concerning Regional Government in Indonesia. This research approach is descriptive normative, basedon secondary data that is evaluated qualitatively using deductive inference. The conclusion of thisresearch is that the power of the acting mayor in carrying out regional government affairs is really notclear and firm because the authority based on the law is not clear and firm, and any Regional Head canbe dismissed due to death, own request, or dismissed.